2019
DOI: 10.1101/581538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transitions in brain-network level information processing dynamics are driven by alterations in neural gain

Abstract: A key component of the flexibility and complexity of the brain is its ability to dynamically adapt its functional network structure between integrated and segregated brain states depending on the demands of different cognitive tasks. Integrated states are prevalent when performing tasks of high complexity, such as maintaining items in working memory, consistent with models of a global workspace architecture. Recent work has suggested that the balance between integration and segregation is under the control of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…Arguably, the storage-transfer decomposition reflects the segregation-integration dichotomy that has long characterized the interpretation of brain function (Sporns, 2010; Zeki & Shipp, 1988). Information theory has the potential to provide a quantitative definition of these fundamental but still unsettled concepts (Li et al, 2019). In addition, information theory provides a new way of testing fundamental computational theories in neuroscience, for example, predictive coding (Brodski-Guerniero et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, the storage-transfer decomposition reflects the segregation-integration dichotomy that has long characterized the interpretation of brain function (Sporns, 2010; Zeki & Shipp, 1988). Information theory has the potential to provide a quantitative definition of these fundamental but still unsettled concepts (Li et al, 2019). In addition, information theory provides a new way of testing fundamental computational theories in neuroscience, for example, predictive coding (Brodski-Guerniero et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing neural gain at intermediate levels of excitability caused an abrupt, non-linear increase in inter-regional synchrony that overlapped with empirical network topological signatures observed when analyzing task-based fMRI data (Shine et al, 2016). This same model was used to demonstrate a gain-mediated increase in inter-regional transfer entropy (Li et al, 2019).…”
Section: Neuromodulating the Manifoldmentioning
confidence: 71%
“…Brain, the input-output curve defining the activity of a slow variable was manipulated in two distinct ways: the sigmoid curve was steepened (left; neural gain) or amplified (right; excitability); b) varying neural gain and excitability caused an abrupt switch in systems-level dynamics --by increasing neural gain, the system shifted from a Segregated state ("S"; low phase synchrony) into an Integrated state ("I"; high phase synchrony); (c) Schematic diagram of functional brain networks in the Segregated (i.e., "S") and Integrated (i.e., "I") phases --in the Integrated state, there are increased connections present between otherwise isolated modules; d) upper panel: an energy landscape, which defines the energy required to move between different brain states: by increasing response gain, noradrenaline is proposed to flatten the energy landscape (red); whereas by increasing multiplicative gain, acetylcholine should deepen the energy wells (green); lower panel: empirical BOLD trajectory energies as a function of mean squared displacement (MSD) and sample time point (TR) of the baseline activity (black) and after phasic bursts in the locus coeruleus (a key noradrenergic hub in the brainstem; red) and the basal nucleus of Meynert (the major source of cortical acetylcholine; green)relative to the baseline energy landscape phasic bursts in the locus coeruleus (red) lead to a flattening or reduction of the energy landscape, whereas peaks in the basal nucleus of Meynert (green) lead to a raising of the energy landscape. Panels a-c adapted from (Li et al, 2019) and Panels d-e adapted from (Munn et al, 2021). Local-to-Global (z).…”
Section: Box 1 -A Spectrum Of Dynamical Systems Approaches In Neuroimagingmentioning
confidence: 99%
“…While the design of our study is not well-suited to support claims about causality, we speculate that by modulating receptor density during the menstrual cycle, hormones may shift the sensitivity of neural circuits, yielding brain states that are increasingly excitable and more likely to produce high-amplitude events [42][43][44]. Indeed, recent studies have demonstrated that the sex hormones estrogen and progesterone differentially influence the density of steroid hormone receptors across the brain throughout the menstrual cycle [45].…”
Section: Discussionmentioning
confidence: 90%